2020
DOI: 10.1186/s13059-020-01982-9
|View full text |Cite
|
Sign up to set email alerts
|

Principles of RNA processing from analysis of enhanced CLIP maps for 150 RNA binding proteins

Abstract: Background: A critical step in uncovering rules of RNA processing is to study the in vivo regulatory networks of RNA binding proteins (RBPs). Crosslinking and immunoprecipitation (CLIP) methods enable mapping RBP targets transcriptome-wide, but methodological differences present challenges to large-scale analysis across datasets. The development of enhanced CLIP (eCLIP) enabled the mapping of targets for 150 RBPs in K562 and HepG2, creating a unique resource of RBP interactomes profiled with a standardized met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
151
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(165 citation statements)
references
References 79 publications
(118 reference statements)
14
151
0
Order By: Relevance
“…RBPs are common across both cell lines. Genome-wide RNA structure profiling showed that 3' untranslated regions (UTR), which are targets for many RBPs, are generally highly structured in cells [29,30]. Therefore, in order to test our pipeline on a robust dataset, we restricted our analysis of RBP binding to 3'UTR regions.…”
Section: Cross-correlation Tracks Reproducibly Cluster Rbp Data Acrosmentioning
confidence: 99%
See 2 more Smart Citations
“…RBPs are common across both cell lines. Genome-wide RNA structure profiling showed that 3' untranslated regions (UTR), which are targets for many RBPs, are generally highly structured in cells [29,30]. Therefore, in order to test our pipeline on a robust dataset, we restricted our analysis of RBP binding to 3'UTR regions.…”
Section: Cross-correlation Tracks Reproducibly Cluster Rbp Data Acrosmentioning
confidence: 99%
“…We selected 29 different RBPs in HepG2 and K562 cells that demonstrate strong, reproducible binding signals at 3'UTRs based on analysis from ref. [30] (Fig. S5A), which came to 40 unique cell type-RBP combinations.…”
Section: Cross-correlation Tracks Reproducibly Cluster Rbp Data Acrosmentioning
confidence: 99%
See 1 more Smart Citation
“…and clustering was performed based on the adjusted p-value for each enriched category using Seaborn ClusterMap. The function, cellular localization, and protein motif information for the RBPs are summarized below using information from (Van Nostrand et al 2020) supplemented by information from mammalian RNA granule and stress granule protein databases (Nunes et al 2019; Youn et al 2019), and AGO1-4 and DICER information from the UniProt database (The UniProt Consortium 2018). RBP are color coded by protein function: red, RNA splicing-related function; orange, miRNA-related functions blue, both an RNA splicing- and a miRNA-related function; black, RBPs whose primary function is not RNA splicing -or miRNA-related.…”
Section: Resultsmentioning
confidence: 99%
“…Quantification helps to assess the true origin of a read segment in the case of multi-mapping. It has been shown that proper quantification of multi-mapped reads led to the discovery of novel protein-RNA interactions from CLIP-seq data [ 32 , 33 ]. A study on RNA-seq data revealed that the expression of genes with multi-mapped reads was underestimated by common quantification methods [ 31 ].…”
Section: Methodsmentioning
confidence: 99%